2015
DOI: 10.7448/ias.18.1.19888
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and behavioural risks for HIV and HCV infections in a population of drug users of Dakar, Senegal: the ANRS 12243 UDSEN study

Abstract: ObjectivesData on the extent of drug use and associated HIV, hepatitis C and hepatitis B infection in West Africa are lacking. The objectives of ANRS12244 UDSEN study were to estimate the size of the heroin and/or cocaine drug user (DU) population living in the Dakar area (Senegal), and assess the prevalence and risk factors of HIV, hepatitis C virus (HCV) and hepatitis B virus (HBV), including behavioural determinants in this population, in order to set up an integrated prevention and treatment programme for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 23 publications
3
21
1
Order By: Relevance
“…The HBsAg prevalence was evaluated by Ndiaye et al [2015] in a military population with 70% of men, and the prevalence was between 9.9% and 12.7% . A recent study in Senegalese drug user (ANRS UDSEN) showed a prevalence of HBsAg (7.9%), similar to ours, on a sample size of (n ¼ 506) [Leprêtre et al, 2015]. Statistical analysis comparing these three recent studies (Table I) did not show a significant difference (P ¼ 0.139).…”
Section: Dear Editorsupporting
confidence: 81%
See 2 more Smart Citations
“…The HBsAg prevalence was evaluated by Ndiaye et al [2015] in a military population with 70% of men, and the prevalence was between 9.9% and 12.7% . A recent study in Senegalese drug user (ANRS UDSEN) showed a prevalence of HBsAg (7.9%), similar to ours, on a sample size of (n ¼ 506) [Leprêtre et al, 2015]. Statistical analysis comparing these three recent studies (Table I) did not show a significant difference (P ¼ 0.139).…”
Section: Dear Editorsupporting
confidence: 81%
“… P 2 is the prevalence obtained by Lô et al [] which is statistically different to that published by Leprêtre et al ().…”
Section: Prevalence Of Hbsag In Senegalcontrasting
confidence: 70%
See 1 more Smart Citation
“…Differences in life expectancy across studies from high-income countries might be partly explained by the proportion of PWID in each population: the two studies with the lowest life expectancy estimates also had the highest proportion of PWID [10,11], whereas life expectancy was highest among studies with fewer PWIDs [8,1214,18]. Although injection drug use has increased in several large African cities [27], data on drug consumption is only rarely reported and generally not systematically assessed. Indeed, no information on IDU was available from the three African studies included in this review.…”
Section: Comparative Life Expectancymentioning
confidence: 99%
“…Prevalence of HCV is very high among DUs group, reaching 22 to 94% in some studies [Fadlalla et al, ]. A recent study in Senegal, showed a prevalence of 23.3% for anti‐HCV antibodies [Leprêtre et al, ], which is very high comparing to HIV‐positive patients (1.6%) [Diop‐Ndiaye et al, ] or blood donors (1.4%) [Dieye et al, ]. However, few data on HCV is available in the country and especially on circulating genotypes and there is a real need to make an update.…”
Section: Introductionmentioning
confidence: 99%